Response of hydrological cycle to recent climate changes in the Tibetan Plateau - Yang, Kun; Ye, Baisheng; Zhou, Degang; Wu, Bingyi; Foken, Thomas; Qin, Jun; Zhou, Zhaoye (Climatic change, 2011)
The Tibetan Plateau (TP) surfaces have been experiencing an overall rapid warming and wetting while wind speed and solar radiation have been declining in the last three decades. This study investigated how climate changes influenced the hydrological cycle on the TP during 1984∼2006. To facilitate the analysis, a land surface model was used to simulate surface water budget at all CMA (China Meteorological Administration) stations on the TP. The simulated results were first validated against observed ground temperature and observation-derived heat flux on the western TP and observed discharge trends on the eastern TP. The response of evaporation and runoff to the climate changes was then analyzed. Major finding are as follows. (1) Surface water balance has been changed in recent decades. Observed precipitation shows insignificant increasing trends in central TP and decreasing trends along the TP periphery while evaporation shows overall increasing trends, leading to decreased discharge at major TP water resource areas (semi-humid and humid zones in the eastern and southern TP). (2) At the annual scale, evaporation is water-limited in dry areas and energy-limited (radiation and air temperature) in wet areas; these constraints can be interpreted by the Budyko-curve. Evaporation in autumns and winters was strongly controlled by soil water storage in summers, weakening the dependence of evaporation on precipitation at seasonal scales. (3) There is a complementary effect between the simulated actual evaporation and potential evaporation, but this complementary relationship may deviate from Bouchet’s hypothesis when vapor pressure deficit (or air temperature) is too low, which suppresses the power of vapor transfer.